2014
DOI: 10.7314/apjcp.2014.15.9.4019
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Combined with Metformin Inhibits Migration and Invasion of Human Nasopharyngeal Carcinoma Cells by Regulating E-cadherin and MMP-9

Abstract: Metformin has been shown to be useful in reducing insulin resistance by restoring sensitivity. Recent evidence suggests that metformin might also possess anti-tumour activity. This study aimed to investigate the effects of cisplatin combined with metformin on the proliferation, invasion and migration of HNE1/DDP human nasopharyngeal carcinoma (NPC) cells, and to provide a new target for treating metastasis. The MTT assay was used to assess viability of HNE1/DDP cells after exposure to different concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…During cancer progression, cancer cells detach from the basement membrane, migrate to and invade surrounding tissues and eventually colonize remote sites (21). A hallmark of cells that have undergone EMT is the loss of the epithelial cell marker E-cadherin and the gain of the mesenchymal cell markers N-cadherin and vimentin (22). Given that the present results revealed that miR-20a increased the EMT-related cell invasion and migration, the next step was to examine the changes in the markers of EMT.…”
Section: Discussionmentioning
confidence: 79%
“…During cancer progression, cancer cells detach from the basement membrane, migrate to and invade surrounding tissues and eventually colonize remote sites (21). A hallmark of cells that have undergone EMT is the loss of the epithelial cell marker E-cadherin and the gain of the mesenchymal cell markers N-cadherin and vimentin (22). Given that the present results revealed that miR-20a increased the EMT-related cell invasion and migration, the next step was to examine the changes in the markers of EMT.…”
Section: Discussionmentioning
confidence: 79%
“…It had been reported that metformin blocked migration and invasion in some malignancies in vitro [35][36][37][38]. However, whether metformin affects these metastasis-related abilities in osteosarcoma is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In a study which aimed to investigate the effects of cisplatin combined with metformin on the proliferation, invasion and migration of HNE1/DDP human nasopharyngeal carcinoma (NPC) cells, and to provide a new target for treating metastasis, it was shown that cisplatin combined with metformin has effects on proliferation, invasion, and migration of human NPC cells (Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%